Kisspeptin and Spexin: lipid profile and sperm parameters in infertile and fertile male subjects - Mohummad Hassan; Mussarat Ashraf; Sher Khan; Farooqui, Nida; Arfa Azhar; Rehman, Rehana (Journal of University Medical & Dental College, 2021)
BACKGROUND & OBJECTIVE: Kisspeptin (KP) and spexin (SPX) are neuropeptides that play a substantial role in metabolism and sexual function. Our objective is to explore the association of spexin and kisspeptin with sperm parameters and lipid profile in the infertile male population. METHODOLOGY: The cross-sectional study was conducted from March 2017 till July 2018 in Aga Khan University Hospital, Karachi, Pakistan, after acquiring ethical approval (4813-BBS-ERC-17). Convenient sampling was applied to recruit 44 normozoospermic subjects as controls and 44 patients with abnormal sperm parameters”. Serum levels of kisspeptin and spexin were measured by enzyme linked immunosorbent assay and Cobas c111 analyzer was used for estimation of high and low density-lipoprotein, triglyceride and serum cholesterol levels. Mann-Whitney U tests and spearman’s rank correlation test were used to analyze quantitative variables, and data was presented by means, standard error (SE) and correlations coefficient, with a statistical significance set at p≤0.05. RESULTS: The mean kisspeptin values of ‘altered sperm parameters’ males 13.23 ± 3.34 were lower than normal sperm parameters 31.89 ± 3.25 (p<0.001). The mean spexin values of altered sperm parameters 383.57 ± 21.09 were less than compared to normal sperm parameters 502.76 ± 19.77 (p<0.001). Correlation of KP and SPX levels was (r-value = 0.332, p= 0.002). There was no significant correlation was found between KP and SPX with lipid profile parameters. CONCLUSION: Spexin and kisspeptin levels observed were higher in male subjects with normal sperm parameters and had a significant positive correlation with each other. There was no impact of spexin on lipid profile and obesity.